Bodies of Clay on Prehistoric Humanised Pottery - Marta Pestarino; Irò B. Camici (Les Carnets de l’ACoSt)
Marta Pestarino and Irò B. Camici review Heiner Schwarzberg and Valeska Becker (eds), Bodies of Clay on Prehistoric Humanised Pottery. Proceedings of the Session at the 19th EAA Annual Meeting at Pilsen, 5th September 2013, Philadelphia: Oxbow Books, 2017